Parasitic Infections among The Refugee of The UNHCR in Ciputat, and Related Risk Factors to The Diseases - Silvia Fitrina Nasution; Ela Laelasari (Jurnal Kesehatan Masyarakat Indonesia, 2021)
Parasitic infections are reported in the most recent years as the disease infected among the refugees from countries with war conflict in Asia and Africa. Several factors have reported as causative agents and routes of transmission of the disease. The objective of the study was to provide epidemiological data of parasitic infections among the UNHCR refugees with some aspects of socio-behavioral and medical history as risk factor to the disease. The design of the study was cross-sectional with a total sampling of the refugees visiting the Puskesmas Pisangan, Ciputat, South Tangerang. We conducted blood diff-count, microscopic examination, and rapid diagnostic tests for the blood; feces by microscopic;while for urine was assayed by dipstick and bacterial culture. The study revealed that there were evidences of parasitic infections in : one patient with positive malaria vivax, one positive patient with non-specific bacteria in urine and with an increased number of leucocyte in the blood (Leucocytosis), also two subjects with higher titer of thrombocyte in their blood (thrombocytosis). Meanwhile, the medical history and transmission profile of the diseases, cultural, social behavior, and other related risk factors to the diseases have shown no strong evidence as a potential disease’s transmission of the parasite from the refugees to their indigenous community.The study has concluded that the evidence of parasitic infections might be at risk of disease’s transmission and should be prevented by a proper response of health services.